Stability of lightly salted fillets during frozen storage - Jóna Sigríður Halldórsdóttir 1989- (2015)
The aim of the project was to study the effect of frozen storage on stability of lightly salted fillets. Atlantic cod (Gadus morhua), was used as model fish, representing lean fish species. An experimental design was set up with two different storage temperatures (-18 and -25°C) and three storage periods (1 week, 3 and 6 months). Two different bleeding methods were used to test the effect of bleeding on product quality (traditional bleeding and insufficient bleeding). The effect of different fillet sizes on product quality after frozen storage was also tested (small fillets and large fillets). Additionally the age of the fish before processing (1 day and 4 days) was also tested. Quality-related changes during frozen storage were measured using the following analysis: water content, water holding capacity (WHC), glazing content, drip loss, color measurement, cooking yield, phosphate content, salt content, total lipid content, free fatty acid content and phospholipid content. A total of 180 fillets of cod were used in this study and a part of those fillets were control fillets (fillets from untreated fish). All the samples were received from two processors. Fish processor A collected the samples in July and fish processor collected the samples in October. Fillets from traditional bled fish had less drip loss and more whiteness compared with fillets from insufficient bled fish. The age of the fish before processing was also an important quality parameter, were 1 day fillets had a much lower yield and also more yellowness on the fillets surface compared to 4 days old fillets. The results showed that large fillet size is more suitable for processing compared to small fillets, where the large fillets had higher lightness value and better cooking yield as well as total yield. Glazing was a conventional method for preventing changes in fillet color. Lightly salted fillets in October had a whiter appearance, better water holding capacity, higher lipid content, higher phospholipid content and lower drip loss, better ...